Single-Gene Phylogeny of Brucella Melitensis in Milk Samples of Ewes in Kalar District, Iraqi Kurdistan Region - Hiwa Yassin Essa; Suha Ali Hussein. (مجلة الانبار للعلوم البيطرية)
The present study aimed to investigate the frequency rate of ovine brucellosis in Kalar district, Iraqi Kurdistan Region and to identify Brucella species in the milk of seropositive ewes via DNA sequencing and phylogenetic analyses. Blood samples were collected from 300 ewes and subjected to the Rose Bengal Plate Test (RBPT), and milk samples of the seropositive animals were collected and underwent a PCR assay using genus- and species-specific primers. Eventually, the positive PCR products were processed for nucleotide sequencing and single-gene phylogenetic analyses. The RBPT revealed a high percentage (11.33%) of seropositive ewes (34 out of 300), and the PCR assay revealed 35.3% (12/34) Brucella genus-positive DNA templates. At the species level, 58.3% (7/12) of templates were positive for the melitensis-specific primers and negative for the abortus and ovis-specific primers, whereas the other five were negative for all species-specific primers used in this study (abortus, melitensis and ovis). The nucleotides sequence of Brucella strains detected in this study showed a 99-100% homology with eight GenBank-published B. melitensis strains, and the single gene phylogenetic analysis showed a close relationship between these strains and the B. melitensis biovar 3 strain NI, China. The high percentage of seropositive ewes showed that brucellosis represents a major obstacle to the animals’ production improvement and a major risk to public health in the Iraqi Kurdistan Region and the single gene phylogenetic analysis confirms its transboundary spread and attracts attention for more strict control programs.